Correlation of CT angiographic pulmonary artery obstruction scores with right ventricular dysfunction and clinical outcome in patients with acute pulmonary embolism - Apfaltrer, Paul; Henzler, Thomas; Meyer, Mathias; Röger, Susanne; Haghi, Dariusch; Grüttner, Joachim; Süselbeck, Tim; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2012)
OBJECTIVE: To correlate CTA pulmonary artery obstruction scores (OS) with right ventricular dysfunction (RVD) and clinical outcome in patients with acute pulmonary embolism (PE). MATERIALS AND METHODS: In a prospective study of 50 patients (66 ± 12.9 years) with PE pulmonary artery OS (Qanadli, Mastora, and Mastora central) were assessed by two radiologists. To assess RVD all patients underwent echocardiography within 24h. Furthermore, RVD on CT was assessed by calculating the right ventricular/left ventricular (RV/LV) diameter ratios on transverse (RV/LVtrans) and four-chamber views (RV/LV4ch) as well as the RV/LV volume ratio (RV/LVvol). OS were correlated with RVD and the occurrence of adverse clinical outcomes (defined as death, need for intensive care treatment, or cardiac insufficiency ≥ NYHA III). RESULTS: Mean Mastora, Qanadli, and Mastora central OS were 26.4 ± 17.7, 12.6 ± 9.9 and 7.5 ± 9, respectively. Echocardiography demonstrated moderate and severe RVD in 10 and 5 patients, respectively. Patients with moderate and severe RVD showed significantly higher Mastora central scores than patients without RVD (14 ± 10.8 vs. 5.9 ± 7.8 [p=0.05]; 17.6 ± 13.2 vs. 5.9 ± 7.8 [p=0.038]). A relevant correlation (i.e. r ≥ 0.6) between OS and CT parameters for RVD were only found for the Mastora score and the Mastora central score (RV/LV4ch: r=0.61 and 0.68, RV/LVvol: r=0.61 and 0.6). 18 patients experienced an adverse clinical outcome. None of the OS differed significantly between patients with and without adverse clinical outcome. CONCLUSION: Pulmonary artery obstruction scores can differentiate between patients with and without RVD. However, in this study, obstruction scores were not correlated to adverse clinical outcome.
Available online 15 September 2011
Gesehen am 29.06.2018